The role of TCGA molecular classification in clear cell endometrial carcinoma - Tang, Xinyue; Hu, Yuanjing (Frontiers in Oncology, 2023)
Clear cell endometrial carcinoma (CCEC) represents a relatively rare and heterogeneous entity. Based on The Cancer Genome Atlas (TCGA) molecular classification, the risk stratification and management of endometrial cancer (EC) have been improved. Although the relationship of CCEC with the TCGA classification is less well understood, data has emerged to suggest that molecular classification plays an important role in the prognosis and management of CCEC. Most of patients with CCEC are characterized by p53abn or NSMP type and the prognosis of these patients is poor, whereas those with MMRd or POLEmut seem to have a favorable prognosis. Adjuvant therapy is recommended in CCEC with p53abn and NSMP. Advanced/recurrent CCEC with MMRd benefit much more from immune checkpoint inhibitors after the failure of platinum-based chemotherapy. In addition, bevacizumab plus chemotherapy upfront seems to improve outcomes of advanced/recurrent patients whose tumors harbored mutated TP53, including CCECs with p53abn. Further studies which exclusively recruit CCEC are urgently needed to better understand the role of molecular classification in CCEC. This review will provide an overview of our current understanding of TCGA classification in CCEC.